Trends in Indigenous and Non-Indigenous Multidomain Well-Being: Decomposing Persistent, Maturation, and Period Effects in Emerging Adulthood. Issue 6 (December 2019) - Parker, Philip D.; Bodkin-Andrews, Gawaian; Parker, Rhiannon B.; Biddle, Nicholas
We explore whether disadvantage exists in domain-specific happiness with Indigenous youth of Australia. Data were collected from 52, 270 Australians aged 15–28 years, 4% of whom were Indigenous, and came from four birth cohorts with data collected between the years 1997 and 2013. Random and fixed effects decomposed differences in well-being into persistent (present at the earliest wave and consistent over time), maturation (changes over age), and period (changes in response to a particular year) components. Results suggested that happiness differences were small to moderate but favored non-Indigenous groups. There were small, persistent differences in happiness with social and future prospects and developmental differences for happiness with life and government. Period effects were observed for happiness with the government. This research reveals that a nuanced approach to Indigenous well-being is needed including not just a multidimensional approach but also one that is sensitive of the means by which disadvantage may emerge.